Evaporation from a Sandy Soil mulches - Gupta, J P (Annals of Arid Zone, 2016)
The results of a field trial at Jodhpur during January, 1977 indicated that in a sandy soil also, mulches play an important role in checking evaporation. Polyethylene has been found to be most effective followed by Organic and rubble mulches in conserving soil moisture.